AquaticVID: a low cost, extended battery life, plug-and-go video system for aquatic research - Lachlan Fetterplace; Peter Ljungberg; Emilia Benavente Norrman; Filip Bohlin; Lisa Sörman; Per Johannesson; Daniel Rooth; Sara Königson (Research Ideas and Outcomes, 2023)
AquaticVID is a low-cost, long battery life video camera system for use in a wide-range of aquatic research applications. The system can be deployed for multiple day recording on a single charge, is submersible to depths of down to 950 m and can be constructed quickly using easily sourced off-the-shelf materials. The system is essentially ‘plug-and-go’, as assembly and preparation for deployment takes < 30 minutes without the need for technical build or programming skills. All of the electrical components are interchangeable with parts from multiple manufacturers and the camera system can be adapted to fit a variety of waterproof enclosure sizes depending on power and data storage requirements. Here, we describe three versions of the AquaticVID in detail and give examples of above and below water research undertaken with the system. The small size and extended battery times, coupled with ease of use and low cost (US$ 268–540) make the AquaticVID a useful option for numerous aquatic research applications.